2022
DOI: 10.1111/anae.15738
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided caudal blockade and sedation for paediatric surgery: a retrospective cohort study

Abstract: Summary Data on safety and success rates of ultrasound‐guided caudal blockade, performed on sedated children with an uninstrumented airway, are scarce. We performed a retrospective observational study of validated data from April 2014 to December 2020 in a paediatric cohort where the initial plan for anaesthetic management was sedation and caudal epidural without general anaesthesia or airway instrumentation. We examined success rates of this approach and rates of block failure and block‐related complications.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Respiratory complications are the most frequent critical events in pediatric anesthesia [ 25 ] in all age groups, given a 3.1% incidence reported across 261 European hospitals (APRICOT; Anesthesia Practice In Children Observational Trial [ 19 ]). The same study found a 1.9% incidence of hemodynamic instability, mainly in the wake of respiratory instability, in 61% of these events [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Respiratory complications are the most frequent critical events in pediatric anesthesia [ 25 ] in all age groups, given a 3.1% incidence reported across 261 European hospitals (APRICOT; Anesthesia Practice In Children Observational Trial [ 19 ]). The same study found a 1.9% incidence of hemodynamic instability, mainly in the wake of respiratory instability, in 61% of these events [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is, however, important to understand that we never modified our strategy of intraoperative and postoperative management in this situation. As stated above, an ever-growing proportion of anesthetic techniques conducted under mild sedation with a natural airway has been evolving at our center over many years [ 25 30 ] and certainly was not a result of special requirements associated with the pandemic, let alone an outcome of modifying our processes under its pressure. Such modifications, therefore, also cannot explain our secondary finding of significantly longer anesthesia durations during the lockdown in early 2020, which most likely was due to constraints in medical staff and a lack of highly experienced pediatric anesthetists during some of those days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This provides anesthesia and analgesia for a significantly longer time than spinal block and has the additional benefit of providing post operative as well as intraoperative analgesia. The utilization of ultrasound guidance for caudal block placement has the advantage of further increasing its success rate 38 . Its regular use in pediatric anesthesia and therefore increased clinician experience, high success rate and excellent safety profile make this a popular choice for infant inguinal hernia surgery.…”
Section: Caudal Blockmentioning
confidence: 99%